2021
DOI: 10.3390/ijerph18073711
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection among the Dental Staff from Lombardy Region, Italy

Abstract: Dentists have been supposed to be among the healthcare workers at greatest risk of SARS-CoV-2 infection. However, scant data are available on the issue. The aim of this study is to quantify the SARS-CoV-2 antibody prevalence and determinants in a sample of dentists, dental hygienists, and other personnel employed among the dental staff in Lombardy region. We used an accurate rapid diagnostic test kit detecting immunoglobulins (Ig) in 504 adults. Of the 499 participants who obtained a valid antibody test, 54 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
6
12
0
2
Order By: Relevance
“…We did not observe any signi cant relationship between sex and SARS-CoV-2 infection, although our data seem to suggest a marginally higher prevalence of infection in males. This is partly in line with a recent systematic review 15 , that found men having a slightly higher frequency of infection 16,17 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We did not observe any signi cant relationship between sex and SARS-CoV-2 infection, although our data seem to suggest a marginally higher prevalence of infection in males. This is partly in line with a recent systematic review 15 , that found men having a slightly higher frequency of infection 16,17 .…”
Section: Resultssupporting
confidence: 89%
“…It is also likely that older people, aware of the higher risks to which they were exposed, were more careful to comply with preventive measures 19 Participants residing in the neighboring provinces of Bergamo and Brescia showed a higher infection rate than participants from the Milan province. These results re ect data from seroprevalence studies in Lombardy 17,20 . In line with other studies 21,22 , compared to married or cohabiting subjects, divorced and separated ones more frequently reported SARS-CoV-2 infection.…”
Section: Resultssupporting
confidence: 77%
“…Furthermore, there is no information on sources of infection. A study among 499 DHW in Lombardy, Italy, conducted from May to September 2020, and aimed at quantifying SARS-CoV-2 antibody prevalence, found 10.8% of DHW to be positive [ 62 ]. Compared with a meta-analysis by Gómez-Ochoa et al, in which the pooled prevalence of SARS-CoV-2 antibodies in HCW was reported to be 7%, this rate is higher [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the frequency of COVID-19-positive tests among dentists and pediatric dentists was 1.9% and 3.0%. Other dental surveys showed that despite the potential high risk for the infection, dentists showed amazingly low rates of COVID-19 in 2020: 0.8% in China [25], 0.9% in USA [26], 10% in Spain [27], and 10.8% in Lombardy in Italy [28]. Despite potential risks, dentists' long tradition in using PPE and infection prevention was rewarded.…”
Section: Discussionmentioning
confidence: 99%